The validity and reliability of global positioning system units for measuring distance and velocity during linear and team sport simulated movements - Huggins, R. A.; Giersch, G. E.; Belval, L. N.; Benjamin, C. L.; Curtis, R. M.; Sekiguchi, Y.; Peltonen, J.; Casa, D. J. (The Journal of Strength and Conditioning Research, 2020)
This experimental study aimed to assess the validity and reliability of shirt-mounted 10-Hz global positioning system (GPS) units (Polar Team Pro) for measuring total distance (TD), constant velocity (VelC), and instantaneous velocity (Veli) during linear running and a team sport simulation circuit (TSSC). Fifteen male soccer athletes completed linear tasks (40 and 100 m) at various velocities: walk (W) (4.8-7.9 km·h-1), jog (J) (8.0-12.7 km·h-1), run (R) (12.9-19.9 km·h-1), and sprint (S) (>20.0 km·h-1) and a 120-m TSSC. Global positioning system validity and reliability for TD, VelC, and Veli were compared with criterion measures using 2 methods (a and b) of GPS raw data extraction. When measuring TD for the Polar Team Pro device, validity and reliability measures were <5% error at all velocities during the 40-m (with the exception of the S [%CV = 8.03]) and 100-m linear trial (both extraction methods) and TSSC. The GPS mean difference (±SD) for TD during the TSSC using extraction methods (a) and (b) was 0.2 ± 1.2 and 2.2 ± 2.2 m, respectively. The validity of the device in measuring VelC was significantly different (p < 0.05) at all velocities during the 40 m (exception W) and the 100 m, with effect sizes ranging from trivial to small (exception of 100 m S). Veli was similar (p > 0.05) at all velocities, except for the W (p = 0.001). The reliability of the device when measuring VelC during the 40 and 100 m was <5% CV; however, during the 100 m, Veli ranged from 1.4 to 12.9%. Despite trivial to large effect sizes for validity of TD, this device demonstrated good reliability <5% CV during linear and TSSC movements. Similarly, effect sizes ranged from trivial to large for VelC, and yet Veli reliability was good for VelC, but good to poor for Veli.